European Stroke Organisation (ESO) guideline on pharmacological interventions for long-term secondary prevention after ischaemic stroke or transient ischaemic attack. (September 2022) - Dawson, Jesse; Béjot, Yannick; Christensen, Louisa M; De Marchis, Gian Marco; Dichgans, Martin; Hagberg, Guri; Heldner, Mirjam R; Milionis, Haralampos; Li, Linxin; Pezzella, Francesca Romana; Taylor Rowan, Martin; Tiu, Cristina; et al.
Recurrent stroke affects 9% to 15% of people within 1 year. This European Stroke Organisation (ESO) guideline provides evidence-based recommendations on pharmacological management of blood pressure (BP), diabetes mellitus, lipid levels and antiplatelet therapy for the prevention of recurrent stroke and other important outcomes in people with ischaemic stroke or transient ischaemic attack (TIA). It does not cover interventions for specific causes of stroke, including anticoagulation for cardioembolic stroke, which are addressed in other guidelines. This guideline was developed through ESO standard operating procedures and the Grading of Recommendations, Assessment, Development and Evaluation (GRADE) methodology. The working group identified clinical questions, selected outcomes, performed systematic reviews, with meta-analyses where appropriate, and made evidence-based recommendations, with expert consensus statements where evidence was insufficient to support a recommendation. To reduce the long-term risk of recurrent stroke or other important outcomes after ischaemic stroke or TIA, we recommend: BP lowering treatment to a target of <130/80 mmHg, except in subgroups at increased risk of harm; HMGCoA-reductase inhibitors (statins) and targeting a low density lipoprotein level of <1.8 mmol/l (70 mg/dl); avoidance of dual antiplatelet therapy with aspirin and clopidogrel after the first 90 days; to not give direct oral anticoagulant drugs (DOACs) for embolic stroke of undetermined source and to consider pioglitazone in people with diabetes or insulin resistance, after careful consideration of potential risks. In addition to the evidence-based recommendations, all or the majority of working group members supported: out-of-office BP monitoring; use of combination treatment for BP control; consideration of ezetimibe or PCSK9 inhibitors when lipid targets are not achieved; consideration of use of low-dose DOACs in addition to an antiplatelet in selected groups of people with coronary or peripheral artery disease and aiming for an HbA1c level of <53 mmol/mol (7%) in people with diabetes mellitus. These guidelines aim to standardise long-term pharmacological treatment to reduce the burden of recurrent stroke in Europe.